Influence of the position on the bicycle on the frontal area in road cyclists - Camara, J.; Maldonado-Martin, S.; Artetxe-Gezuraga, X. (Collegium Antropologicum, 2012)
The aims of the present study were to determine whether the estimations of the frontal area of the combined cyclist-bicycle (APCB) obtained with the Heil`s non-logarithmic prediction equations (NPE) in the stem position (SP), brake hoods position (BHP) and drops position (DP) are comparable to the measured APCB with the computerized planimetry (CP) method, and to analyse with the CPmethod and the NPE the influence of the body position on the APCB. Nineteen participants competing in the Spanish Road Cycling First division took part in the study. The NPE overestimated the APCB in the BHP and in the DP compared with the measured APCB with the CP method (6.9% and 5.1%, respectively; p<0.05). Significant differences among the three positions were obtained with the CP method. The overestimation of the APCB with the NPE in the BHP and in the DP, and the less sensitivity of the NPE to show significant differences between the SP and DP suggest that the NPE are not appropriate to accurately predict the APCB.